Dysregulated tryptophan metabolism: driving T cell subsets and PI3K-Akt pathway alterations in Hashimoto’s thyroiditis - Zhang, Lijian; Zhou, Xinrui; Cheng, Tingwei; Wang, Qiong; Pei, Xiaoyan; Yu, Lei; Jin, Guoxi (Frontiers in Immunology, 2025)
PurposeThis study explored the role of tryptophan (Trp) metabolism in Hashimoto’s thyroiditis (HT) pathogenesis using clinical samples and animal models, given the unclear mechanisms and limited treatments of HT.MethodsClinically, serum Trp, lactic acid, and alanine levels in 10 HT patients and 10 healthy controls were measured by ELISA. In animal experiments, female C57BL/6 mice were divided into Con, HT, HT+T (Trp supplemented), and HT+I (Trp metabolism inhibitor IDO1/TDO-IN-4 treated) groups. After inducing autoimmune thyroiditis, various tests were conducted, including ELISA for inflammation factors, HE staining for thyroid pathology, flow cytometry for T cell subsets, RNA-seq for gene expression, Western Blotting for PI3K-Akt pathway proteins, and CIBERSORT for immune cell analysis.ResultsHT patients had significantly lower serum Trp levels. The HT group showed thyroid damage and increased inflammation factors. Trp supplementation alleviated thyroid damage and reduced inflammation factors, while the inhibitor worsened them. Trp also regulated T cell subsets and immune cell environment. RNA-seq and Western Blotting indicated Trp’s impact on immune response and PI3K-Akt pathway.ConclusionTrp metabolism abnormality is associated with HT. Trp supplementation can alleviate HT progression by regulating T cell function and the PI3K-Akt pathway, while inhibiting Trp metabolism exacerbates it. This suggests Trp metabolism’s potential as a therapeutic target for HT.